Digital Asynchronous Phase Locked Loop for Precision Control of MOEMS Scanning Mirror. Issue 15 (2019) - Brunner, David; Yoo, Han Woong; Schitter, Georg
Abstract: Accurate phase detection and control of nonlinear resonant MOEMS mirrors are crucial to achieve stable scanning motions and high resolution imaging as needed in precision applications such as lidar systems. This paper proposes a novel digital PLL that uses an asynchronous logic for high precision driving of the MOEMS mirror and immediate phase compensation, while the clock speed is kept low. The phase of the mirror is detected by an amplified current signal, generated by the movement of the comb-drive electrodes and a simple comparator circuit. An analysis of the proposed detection method shows that the optical standard deviation of the system scales inversely proportional with the product of the driving voltage, the curvature of the comb-drive capacitance and the angular velocity of the MOEMS mirror at the zero crossing. The low phase detection standard deviation of 2.94 ns, in closed loop operation corresponds to a maximum optical standard deviation of 1mdeg at 55.6° field of view and a scanning frequency of 2kHz.